ANALYSIS OF THE OPPOSITE REACTIVE POWER DIRECTION PHENOMENON ON TWO PARALLEL OVERHEAD TRANSMISSION LINES - Tolić Ivan; Nađ Robert; Hartmann Tolić Ivana (Journal of Energy Technology, 2024)
This paper presents an analysis of the opposite reactive power direction phenomenon on two parallel overhead transmission lines. Measurements are performed on transmission lines, recorded using energy meters. Superficial reasoning leads to the conclusion that the measurement system is not trustworthy. In addition, more detailed theoretical analysis shows that the phenomenon is possible and it is not the result of the incorrect measurement, but it is the result of reactive power distribution along the respective transmission lines.